2004
DOI: 10.1051/0004-6361:200400046
|View full text |Cite
|
Sign up to set email alerts
|

Millimeter dust emission from an SMC cold molecular cloud

Abstract: Abstract. We presented SIMBA 1.2 mm continuum observations of SMCB1-1 an SMC molecular cloud known to be distant from massive ionizing stars. The gas mass derived from the SIMBA flux is a factor of ∼10 higher than the virial mass previously reported from CO observations. We propose an interpretation where the virial mass underestimates the total mass because the CO emission comes from dense clumps which do not trace the full cloud area and velocity distribution. This work sets an important question for the und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
51
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 19 publications
6
51
0
Order By: Relevance
“…Because of the wavelength dependence of thermal dust emission, millimeter dust emission is often used as a tracer of the cold molecular gas reservoir in a galaxy (e.g. Guelin et al 1993;Dunne & Eales 2001;Rubio et al 2004;Weiß et al 2008;Vlahakis et al 2008). This information is particularly interesting since cold H 2 is almost impossible to observe and the use of CO line emission is not straightforward, especially at low metallicities (Israel 1988;Lequeux et al 1994;Israel 1997b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the wavelength dependence of thermal dust emission, millimeter dust emission is often used as a tracer of the cold molecular gas reservoir in a galaxy (e.g. Guelin et al 1993;Dunne & Eales 2001;Rubio et al 2004;Weiß et al 2008;Vlahakis et al 2008). This information is particularly interesting since cold H 2 is almost impossible to observe and the use of CO line emission is not straightforward, especially at low metallicities (Israel 1988;Lequeux et al 1994;Israel 1997b).…”
Section: Introductionmentioning
confidence: 99%
“…This information is particularly interesting since cold H 2 is almost impossible to observe and the use of CO line emission is not straightforward, especially at low metallicities (Israel 1988;Lequeux et al 1994;Israel 1997b). Millimeter dust emission could be a good alternative to the CO molecule for tracing cold matter, also in lowmetallicity environments (Thronson 1988;Israel 1997a;Rubio et al 2004;Bot et al 2007Bot et al , 2010. This simple picture is, however, thrown into doubt by observations of the Milky Way and nearby galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…This result was also found in studies of several molecular clouds in the SW region of the SMC Bar by Bot et al (2007) as well as in the active star forming region N 66 (Perez 2006). The analysis of observations of the SMC has shown for many clouds in the same region that the masses of gas deduced from the dust emission were ten times higher than those deduced by the application of the virial theorem using the size of the clouds and the gas velocity dispersion measured in CO (Rubio et al 2004;Bot et al 2007; fig. 1 of Bot et al, these proceedings).…”
Section: Molecular Massmentioning
confidence: 90%
“…The first 1.2-mm continuum observations of molecular clouds in the Magellanic Clouds were done with the SIMBA bolometer at the SEST telescope in La Silla, Chile. In the SMC, Rubio et al (2004) reported the results for a cold quiescent cloud in which they found that the gas mass derived from the continuum dust emission was larger than the virial mass determination of the cloud. This result was also found in studies of several molecular clouds in the SW region of the SMC Bar by Bot et al (2007) as well as in the active star forming region N 66 (Perez 2006).…”
Section: Molecular Massmentioning
confidence: 99%
See 1 more Smart Citation